The Effect of Group Investigation Model on Reading Comprehension and Critical Thinking Skills of Grade V Elementary School Students - Sumarni Bamabang (PT Mattawang Mediatama Solution, 2023)
This study aims to determine the effect of Group Investigation learning model on the ability to read the understanding of elementary students in the text of discourse material. Research subjects consisted of two schools namely SDN 47 as the experimental class and SDN Krisik 48 as the control class. Research subjects were determined based on pretest and posttest mean values. The research design used in this research is a quasi-research field (Quasi Eksperimen) involving control and experimental group, with non Equivalent Control Group Design research design. Students' reading comprehension skills are measured using multiple choice tests. The measurement data was analyzed using t-test with the help of SPSS 16.0 for Windows program. The result of the research showed that the average percentage of the improvement of study of Group Investigation model on students' reading comprehension was 76.33 higher than the students who studied with conventional learning. Technique of data analysis of research done by descriptive analysis and statistical analysis using t-test with significance 0,050 for hypothesis test.